In-hospital Pediatric Endoscopic Retrograde Cholangiopancreatography Is Associated With Shorter Hospitalization for Children With Choledocholithiasis. Issue 1 (January 2019) - Bonasso, Patrick C.; Gurien, Lori A.; Staszak, Jessica; Gowen, Marie E.; Troendle, David M.; Odiase, Eliane; Lazar, Lauren; Ruan, Wenly; Barth, Bradley A.; Williams, Regan F.; Dassinger, Melvin S.
ABSTRACT: Objectives: Children with choledocholithiasis are frequently managed at tertiary children's hospitals that do not have available endoscopic retrograde cholangiopancreatography (ERCP) proceduralists. We hypothesized that patients treated at hospitals without ERCP proceduralists would have a longer hospital length of stay (LOS) than those with ERCP proceduralists. Methods: Charts were reviewed for patients who underwent cholecystectomy and ERCP at 3 tertiary children's hospitals over 10 years. Trauma and complicated pancreatitis patients were excluded. Comparisons between patients requiring and not requiring transfer for ERCP were made using Wilcoxon rank-sum tests for continuous variables and Fisher's exact tests for categorical variables. Results: One hundred and sixty-four children underwent ERCP for suspected choledocholithiasis: 79 (48%) in the transfer group and 85 (52%) in the no transfer group. Median LOS was longer for patients requiring transfer (7 vs 5 days, P  < 0.0001). One-third (34%) of the transfer patients had magnetic resonance cholangiopancreatography compared to only 7% that did not require transfer ( P  < 0.0001). Among the 123 patients who underwent ERCP before cholecystectomy, 53% required (66/123) transfer and 47% (57/123) did not. Transfer group patients had longer median hospital LOS ( P  < 0.0001), more days between admission and ERCP ( P  < 0.0001), and more days between ERCP and surgery ( P  = 0.0004). Conclusions: Overall median LOS was significantly shorter for patients who underwent ERCP at the admitting facility. Patients who underwent ERCP before cholecystectomy at hospitals without available ERCP proceduralists incurred longer LOS. There is a need for more pediatric proceduralists appropriately trained to perform ERCP in children.